2008
DOI: 10.3892/mmr.1.4.571
|View full text |Cite
|
Sign up to set email alerts
|

SPARC-like1 mRNA is overexpressed in human uterine leiomyoma

Abstract: Abstract. Uterine leiomyomas (ULs), also known as fibroids, are benign and monoclonal tumors frequently found in the female population. The genetic alterations that contribute to UL tumor development have not been well established, and the goal of this study was to reveal gene expression variation between ULs and healthy uterine tissue. We compared the gene expression profiles of 13 UL tumors with that of their adjacent normal tissue using the Differential Display mRNA assay (DDRT-PCR). Among the genes upregul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…2A ). In addition, the associations identified in the present review, between SPARCL1 and invasiveness, metastasis and drug resistance of cancer, were consistent with previous studies ( Table I )( 9 – 16 , 18 26 ). Furthermore, analysis indicated that SPARCL1 may participate in cancer development and progression, in 9 biological processes (P<0.001) including cell viability, cell cycle, migration and adhesion ( Fig.…”
Section: Sparcl1 Contributes To Tumor Development and Progressionsupporting
confidence: 92%
“…2A ). In addition, the associations identified in the present review, between SPARCL1 and invasiveness, metastasis and drug resistance of cancer, were consistent with previous studies ( Table I )( 9 – 16 , 18 26 ). Furthermore, analysis indicated that SPARCL1 may participate in cancer development and progression, in 9 biological processes (P<0.001) including cell viability, cell cycle, migration and adhesion ( Fig.…”
Section: Sparcl1 Contributes To Tumor Development and Progressionsupporting
confidence: 92%
“…Particularly, growing evidence shows that SPARCL1 often presents a reduced or absent expression pattern in a variety of human tumor tissues (Bendik et al, 1998;Nelson et al, 1998;Isler et al, 2004;Esposito et al, 2007;Zaravinos et al, 2011;Hurley et al, 2012;Li et al, 2012). However, several studies have also found that an increased expression of SPARCL1 in a few of other type of human tumors derived from liver (Lau et al, 2006), uterus (Mencalha et al, 2008), and colon and rectum (Zhang et al, 2011;Hu et al, 2012). All these conflicting findings suggest that SPARCL1 is indeed implicated in human cancer development and progression, but its expression pattern may be in a tissue-specific manner.…”
Section: Discussionmentioning
confidence: 99%
“…SPARCL1 has been described in many cellular processes 14, including development, tissue regeneration, and cancer, though data concerning it in cancer have been controversial 15–17. In addition, its role in GC is still unknown.…”
Section: Introductionmentioning
confidence: 99%